MINIMIZING THE TURNOVER INTENTION BY EMPLOYEE DEVELOPMENT IN GARMENT COMPANIES - Kurniawati, Sinta Ayu; Wahyuni, Sari (Universitas Brawijaya, Indonesia, 2019)
The aim of this study is to determine the role of employee development carried out by garment companies to minimize the emergence of turnover intention among garment workers in Indonesia. This study using survey data conducted by the collaborations between the University of Indonesia (UI), Tufts University (TU), Better Work-ILO (BW) and Real-TimeAnalytics (RTA) Vietnam, which is collected from 109 garment companies and 2580 respondents in the garment sector. The data were analyzed using structural equation models (SEM) with Lisrel 8.8. The results show that employee development is able to increase the growth mindset and empowerment perceived by workers, therefore reduce turnover intention among workers in the garment industry. However, the findings also reveal that it turns out that employee development cannot improve the job security perceived by workers. These results provide significant input to human resource development in Indonesia. Further studies may consider the effect of the growth mindset on job security. It is expected that employee development will have a positive impact on empowerment as well as job security through a growth mindset which ultimately minimizing the emergence of turnover intention.